2023
DOI: 10.1039/d3qm00109a
|View full text |Cite
|
Sign up to set email alerts
|

Functional conductive hydrogels: from performance to flexible sensor applications

Abstract: Due to the good biocompatibility and easy regulation of hydrogels, hydrogel-based flexible sensors have flourished in the fields of wearable electronics, electronic skin, and soft robotics in recent years. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 204 publications
0
15
0
Order By: Relevance
“…The synthetic procedure was modified from ref . Gelatin (3.00 g) was dissolved in phosphate-buffered saline solution (60 mL) and placed in a reflux system at 50 °C until the solution became fully dissolved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic procedure was modified from ref . Gelatin (3.00 g) was dissolved in phosphate-buffered saline solution (60 mL) and placed in a reflux system at 50 °C until the solution became fully dissolved.…”
Section: Methodsmentioning
confidence: 99%
“…Several strategies have been employed to prepare conductive hydrogels, including using conductive fillers/dopants, conductive monomers, or polymers, introducing free ions, and incorporating new conductive network structures. For this study, conductive monomers were selected as they offer both conductivity and the ability to cross-link with other polymers. This combination can also serve as a scaffold, facilitating better regulation of the physical and mechanical properties of the hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, durability has been shown to be a limiting concern for applications based on MXene, and it has been demonstrated that synthesizing MXene into hydrogels considerably improves the stability of these applications. Because of their one-of-a-kind and intricate gel structure as well as their distinct method of gelation, MXene hydrogels call for extensive investigation and innovation at the nanoscale level . Although there has been a significant amount of research conducted on the use of MXene-based composites in electronics, the synthesis techniques and utilization of MXene-based hydrogels for wearable electronics are still rather uncommon.…”
Section: Mxene-based Wearable Electronicsmentioning
confidence: 99%
“…Consequently, CHs have become ideal candidates for wearable sensors. Generally, they should have a combination of three features to precisely transform human movements into detectable signals 7,9,[19][20][21][22][23] : (i) skin-comparable mechanical properties and selfadhesive capability to avoid motion artifacts, (ii) stable and high sensitivity to transform human motions into electrical signals, and (iii) low detect limit and quick response to recognize subtle movements. Despite successful achievements in CHs, this combination remains difficult to realize.…”
Section: Introductionmentioning
confidence: 99%